2009
DOI: 10.1002/adma.200900187
|View full text |Cite
|
Sign up to set email alerts
|

Translating Electronic Currents to Precise Acetylcholine–Induced Neuronal Signaling Using an Organic Electrophoretic Delivery Device

Abstract: A miniaturized organic electronic ion pump (OEIP) based on conjugated polymers is developed for delivery of positively charged biomolecules. Characterization shows that applied voltage can precisely modulate the delivery rate of the neurotransmitter acetylcholine. The capability of the device is demonstrated by convection‐free, spatiotemporally resolved delivery of acetylcholine via a 10 µm channel for dynamic stimulation of single neuronal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
153
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(158 citation statements)
references
References 30 publications
1
153
2
Order By: Relevance
“…The popularity of PEDOT:PSS comes from the fact that it can be solution-processed and therefore be manufactured using low cost procedures, such as printing techniques, [19] on a wide variety of substrates (plastic, [16,17] paper, [18] woven fabric, [19] ...), is commercially available, has a relatively high conductivity and is proven to be biocompatible. [20] Recently, OECTs have been used to create cell-density gradients, [21] to measure barrier tissue integrity [22] and to monitor action potentials in rat brains, [23] but also much efforts have been dedicated to utilize PEDOT:PSS in OECTs for biosensor applications.…”
mentioning
confidence: 99%
“…The popularity of PEDOT:PSS comes from the fact that it can be solution-processed and therefore be manufactured using low cost procedures, such as printing techniques, [19] on a wide variety of substrates (plastic, [16,17] paper, [18] woven fabric, [19] ...), is commercially available, has a relatively high conductivity and is proven to be biocompatible. [20] Recently, OECTs have been used to create cell-density gradients, [21] to measure barrier tissue integrity [22] and to monitor action potentials in rat brains, [23] but also much efforts have been dedicated to utilize PEDOT:PSS in OECTs for biosensor applications.…”
mentioning
confidence: 99%
“…When hydroxide ions are transported from the emitter into the junction the proton concentration decreases together with IC. We have recently shown that organic conducting materials can be used in vitro and in vivo to translate electric signals into precise delivery of positively charged chemical messengers 2,[23][24] . To evaluate if the present npn-IBJT can be used in a corresponding manner, i.e.…”
mentioning
confidence: 99%
“…[1][2] One example is organic electronic ion pumps, 15 which are able to precisely control the flow of ions between two reservoirs, and have been used to pump neurotransmitters and stimulate cochlear cells in the inner ear of a guinea pig. [3][4][5] Another example is organic electrochemical transistors (OECTs) that are being developed for a variety of biosensing 20 applications, including the detection of ions, [6][7][8] metabolites (such as glucose 9 and lactate 10 ) and antibodies. 11 Originally developed by Wrighton in the 80's, 12 OECTs consist of a conducting polymer film (channel of the transistor) in contact with an electrolyte.…”
mentioning
confidence: 99%
“…The experiments involved placing a small amount (1.43 µl) of [P 1,4,4,4 ][Tos] that included the enzyme glucose oxidase (GOx, 500 unit/ml) and the mediator ferrocene [bis (n5-35 cyclopentandienyl) iron] (Fc, 10 mM) on the centre of the device and allowing it to be accommodated in the hydrophilic virtual wells. Subsequently, 50 µl of glucose solution in PBS were added to the device and allowed to mix with the RTIL solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation